Production and productivity of cattle for meat and milk in Costa Rica from 1984 to 2014 - Morales Abarca, Luis Fernando (2018)
The research was conducted in order to determine the evolution of the production and productivity of vaccine livestock for meat and milk, in Costa Rica, in the period from 1984 to 2014, for which official data of the United Nations Organization for Food and Agriculture (FAO) were used and were consulted for information from the National Livestock Corporation (CORFOGA) and the National Chamber of Producers of Milk (CNPL). Analysis of production showed a performance lagged in meat cattle, while dairy farming activity presented a constant growth throughout the study period. In terms of productivity, in the case of meat cattle was determined a fluctuating behavior, which presented low yields due to limiting factors of the activity; While the productivity of milk cattle showed positive results.